(untitled) (Journal of Event, Tourism and Hospitality Studies, 2025)
The tourism industry is a significant contributor to greenhouse gas emissions and climate change. The future of environmental sustainability depends highly on today’s youth. It is therefore crucial that young people today actively participate in dealing with environmental issues besides conserving natural resources by acting responsibly towards the environment. This engagement will ensure ecological sustainability and the ability to meet the needs of future generations. In Malaysia, youth constitute almost half of the total population, hence highlighting the importance of their leadership in environmental sustainability initiatives, and the need to recognize their perspectives. Data for this study was collected from 90 youths aged between 20 to 24 years old. All the responses were categorised into four main themes namely, governance for environmental sustainability, education to enhance awareness, acculturation of environmentally friendly practices and involvement of all stakeholders. To the authors’ knowledge, this is among the first studies in Malaysia to examine the youth’s point of view on strategies for sustaining the environment.